New antibacterial, antifungal and antioxidant agents bearing sulfonamide - Regina Chinelo Ochu; Uchechukwu Chris Okoro; Jeanet Conradie; David Izuchukwu Ugwu (Elsevier, 2024)
The successful nickel catalyzed synthesis of N-(aryl) substituted p-toluene sulphonamides is reported. The intermediate 4-methylbenzenesulphonamide was obtained by the reaction of p-toluenesulphonyl chloride and ammonium hydroxide. Substituted p-toluene sulphonamides were obtained by coupling 4-methylbenzenesulphonamide with readily available aryl halides via Buchwald-Hartwig cross-coupling reaction. The structures of the compounds were confirmed using Fourier Transform Infrared (FT-IR), proton NMR, carbon-13 NMR and mass spectroscopy. The new compounds were screened for antibacterial and antifungal activities against Bacillus subtilis, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, Candida albicans and Aspergillus niger using agar diffusion technique. Some of the compounds showed improved antimicrobial activity when compared with ciprofloxacin and ketoconazole. The sulphonamides were further screened for antioxidant activity using 1,1-diphenyl-2-picrylhydrazide (DPPH), ferric reducing antioxidant potency (FRAP) and ferrous sulphate induced lipid peroxidation. The compounds showed improved antioxidant activity on comparison with ascorbic acid. Specifically, compound 20 was revealed by this study to be a lead antibacterial and antifungal agent whereas compound 17 showed a lead as antioxidant agent. The drug-likeness study indicated that none of the compounds violated Lipinski, Ghose, and Verber rules for drug-able molecules.